Endometrial cancer arising after complete remission of uterine malignant lymphoma: A case report and mutation analysis - Ikumi Kuno; Hiroshi Yoshida; Takashi Kohno; Atsushi Ochiai; Tomoyasu Kato (Elsevier, 2019)
Uterine malignant lymphoma is rare and its association with secondary cancer has not been fully described. Here, we report a rare case of endometrial cancer arising after 1 year of complete remission of uterine diffuse large B-cell lymphoma (DLBCL). An 88-year-old woman was referred to us for abnormal genital bleeding and was diagnosed with uterine DLBCL. She underwent chemotherapy comprising rituximab with cyclophosphamide, doxorubicin, vincristine, and prednisolone followed by radiation therapy; subsequently, she achieved complete remission. One year later, she noticed genital bleeding recurrence, and endometrial biopsy revealed endometrial adenocarcinoma. Total hysterectomy and bilateral salpingo-oophorectomy were performed. Her pathological diagnosis was endometrial endometrioid carcinoma, grade 1 (pT1aN0). Adenocarcinoma was observed over foamy macrophages aggregates, indicating remission of DLBCL. Targeted sequencing of both DLBCL and endometrial cancer revealed 24 gene mutations including the truncation-type mutations of ARID1A and PTEN occurring only in endometrial cancer. These multiple somatic gene mutations accumulating within 1 year imply endometrial carcinogenesis induced by DNA damages caused by treatment for DLBCL. Although the epidemiological risk of secondary malignancies after uterine lymphoma remains unclear, the present case serves as a warning for secondary cancer and highlights the importance of early detection and treatment. Keywords: Chemo-radiotherapy, Endometrial cancer, Mutation analysis, Secondary cancer, Uterine malignant lymphoma